Corrosion Behavior of Modified F/M Steel with Ti and Dispersed Oxides: Y2O3 and ZrO2 Under High Temperature in Static Liquid Lead - Setyo Hadi, Dhimas; Wafda, Hakimul; Pramutadi Andi Mustari, Asril; Trisnawan, Veri; Widiawati, Nina; Miftasani, Fitria; Hadi Prajitno, Djoko (Science and Technology Indonesia, 2025)
This study investigates the corrosion resistance of Oxide Dispersion Strengthened (ODS) steel in a lead environment, which is crucial for Lead-Cooled Fast Reactors (LFR), a type of Generation IV nuclear reactor. To improve corrosion resistance, two types of oxides-yttrium oxide (Y2O3) and zirconium oxide (ZrO2)-were added individually and in combination to the ODS steel. The samples were synthesized via powder metallurgy and characterized using optical microscopy, X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX), and Vickers hardness testing. Corrosion testing was conducted in static liquid lead at 550°C for 75 hours. The results showed that the addition of Y2O3 and ZrO2 significantly refines grain structure, increases hardness, and promotes the formation of stable, protective oxide layers. Particularly, the dual-oxide (Y2O3+ ZrO2) sample exhibited the most uniform and effective oxide barrier, indicating improved resistance to lead corrosion. These findings demonstrate that dual-oxide dispersion is a promising strategy for improving the durability of structural materials in LFR applications.